2016
DOI: 10.1093/nar/gkw099
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic triangle of HMGA2, LIN28B and IGF2BP1 antagonizes tumor-suppressive actions of the let-7 family

Abstract: The tumor-suppressive let-7 microRNA family targets various oncogene-encoding mRNAs. We identify the let-7 targets HMGA2, LIN28B and IGF2BP1 to form a let-7 antagonizing self-promoting oncogenic triangle. Surprisingly, 3′-end processing of IGF2BP1 mRNAs is unaltered in aggressive cancers and tumor-derived cells although IGF2BP1 synthesis was proposed to escape let-7 attack by APA-dependent (alternative polyadenylation) 3′ UTR shortening. However, the expression of the triangle factors is inversely correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(166 citation statements)
references
References 67 publications
(133 reference statements)
14
145
2
Order By: Relevance
“…IMP family members are commonly re-expressed in tumor cells that contain one or both of the LIN28 paralogs (Busch et al 2016;our unpublished observations). In ovarian cancer cell lines, LIN28B and IMP1 appear to display synergistic protection of let-7 target transcripts, including HMGA2, as well as mutual protection, as they are both let-7 targets (Busch et al 2016).…”
Section: Regulation Of Imp Expressionmentioning
confidence: 94%
See 2 more Smart Citations
“…IMP family members are commonly re-expressed in tumor cells that contain one or both of the LIN28 paralogs (Busch et al 2016;our unpublished observations). In ovarian cancer cell lines, LIN28B and IMP1 appear to display synergistic protection of let-7 target transcripts, including HMGA2, as well as mutual protection, as they are both let-7 targets (Busch et al 2016).…”
Section: Regulation Of Imp Expressionmentioning
confidence: 94%
“…Several recent studies have shown that one mechanism by which IMPs promote mRNA stability is by preventing miRNA-mediated silencing (Elcheva et al 2009;Goswami et al 2010;Nishino et al 2013;Busch et al 2016;Degrauwe et al 2016). IMP1 was notably observed to promote the expression of the self-renewal factor and let-7 miRNA family target HMGA2 (for review, see Fusco and Fedele 2007), which raised the possibility that IMP1 may counteract let-7 miRNA action during development and thereby contribute to stem cell maintenance (Nishino et al 2013).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA and protein expression patterns of BCL11A and HMGA2 suggest that IGF2BP1 is a posttranscriptional regulator of both proteins. The posttranscriptional up-regulation of HMGA2 was expected because IGF2BP1 is a known competitor of let-7 for HMGA2 mRNA binding (31).…”
Section: Igf2bp1 Overexpression Reverses Adult Erythroblasts To a Mormentioning
confidence: 99%
“…Also an oncofetal protein, IGF2BP1 is commonly detected in several tumors. Its effects upon growth are variable with speculation of both oncogenic as well as tumorsuppressive functionality (31,(44)(45)(46) based upon the cellular context of its expression. As shown here, overexpression of IGF2BP1 in the committed erythroblasts did not prevent their maturation or enucleation in ex vivo cultures.…”
Section: Bcl11a Is Posttranscriptionally Regulated In Igf2bp1 Overexpmentioning
confidence: 99%